Distorted Communication, Unequal Representation: Constituents Communicate Less to Representatives Not of Their Race. Issue 2 (8th October 2013) - Broockman, David E.
<x xml:space="preserve">Abstract</x> Communications from constituents strongly shape the representation politicians provide. However, if politicians hear less from some constituents than others, this unequal communication may lead to unequal representation. In this article, I present a field experiment demonstrating that constituents are less likely to communicate to representatives not of their race. The experiment exploited electoral rules in Maryland, where several multimember districts have both black and white representatives. I provided 8, 829 residents of such districts an opportunity to communicate to one of their actual representatives, whose race I randomized. Both blacks and whites were markedly less likely to communicate to their representatives not of their race. These results imply that politicians receive racially distorted communication, hearing disproportionately infrequently from constituents unlike them. The fact that most racial minorities have white representatives may thus help explain both minorities' less frequent communication to their representatives and the diminished substantive representation minorities typically receive.